Tun Sri Lanang (1565-1659) and His Contributions in Aceh - Nordin, Shah Rul Anuar; Sabtu, Muhamad Helmy (Journal of Techno-Social, 2022)
Many scholars wrote about Tun Sri Lanang as a Prime Minister during Johor Sultanate and about his monumental book, Sulalah al-Salatin. However, people lack informations about Tun Sri Lanang’s contribution during his life in Aceh. Thus, this study aims to identify Tun Seri Lanang’s contribution to the Acehnese in the 17th century. In this study, the researchers used a qualitative method. Data is analyzed using content analysis methods from interviews and sources from books, documents and journals. The finding shows that Tun Seri Lanang contributed greatly as a community leader, scholar, writer, advisor to the sultan/ sultanah of Aceh and left honorable descendants until today. The researchers hope that this study can further enrich the literature about Malay figures in the 17th century. Even so, this kind of writing should be intensify as a reference for the next generations. Keywords: Tun Seri Lanang, Contributions, Aceh